Interactive approaches to anti-racist Christian praxis: Participative Black Theology - Reddie, Anthony (Handelingen: Tijdschrift voor Praktische Theologie en Religiewetenschap, 2023)
In this essay I will be addressing the issue of how a participative model of Black Theology has been utilised in order to assist predominantly white students training for public, authorised ministry in Britain to better understand the challenges and ethical commitments to being anti-racist Christian disciples and allies alongside their black brothers and sisters in the ‘Body of Christ’.